Pulmonary Pathology Neoplastic and Non-Neoplastic (Encyclopedia of Pathology,, 2018)
This book covers the complete field of pulmonary pathology - neoplastic and non-neoplastic - from Acinic cell tumor in the lung to Wegener`s Granulomatosis. The alphabetically arranged entries, each of which provides a detailed description of a specific pathological disease pattern, allow readers to quickly and easily find the information they need. .